2018
DOI: 10.4103/jnrp.jnrp_323_17
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aging on Nerve Conduction Velocities and Late Responses in Healthy Individuals

Abstract: Background:Nerve conduction studies are performed to diagnose the disorders of the peripheral nervous system. The reference values for nerve conduction velocity (NCV) and late responses for different nerves considerably vary in different group and type of population. Physiological factors such as age, temperature, height, and gender affect the NCV. However, there are very few studies which show the age group at which these changes become significant.Aim and Objectives:The aim of the study was to establish the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 12 publications
6
43
2
4
Order By: Relevance
“…Furthermore, the presence of non-neuronal cell bodies in co-culture spheroids decreases the probability of recording from the appropriately stimulated cell bodies. Importantly, NCV from hNs was found to be considerably lower as compared to the NCV values obtained in human patients [31][32][33] . This is not particularly surprising, considering an in vitro system, at room temperature, comprised of iPSC-derived neurons that are less mature as compared to mature, myelinated axons of nerves assessed in vivo.…”
Section: Evaluation Of Nerve Conduction Velocity (Ncv)contrasting
confidence: 55%
“…Furthermore, the presence of non-neuronal cell bodies in co-culture spheroids decreases the probability of recording from the appropriately stimulated cell bodies. Importantly, NCV from hNs was found to be considerably lower as compared to the NCV values obtained in human patients [31][32][33] . This is not particularly surprising, considering an in vitro system, at room temperature, comprised of iPSC-derived neurons that are less mature as compared to mature, myelinated axons of nerves assessed in vivo.…”
Section: Evaluation Of Nerve Conduction Velocity (Ncv)contrasting
confidence: 55%
“…Because SNAP and CMAP amplitudes decrease with age and DML lengthens, it is possible that, given that we used the same “normal” cutoff values in both groups, some elderly patients could have been misclassified electrodiagnostically as being more severe than they truly were. Although the magnitude of this effect is likely to have been small, it may have been significant …”
Section: Discussionmentioning
confidence: 99%
“…Although the magnitude of this effect is likely to have been small, it may have been significant. [29][30][31] We chose to use Pearson's correlation coefficient to examine the relationship between variables in our study. The small sample size and skewed disease distribution toward the severe end in our elderly population may have had an impact on our correlation measures.…”
Section: Discussionmentioning
confidence: 99%
“…Disfunction of spinal motor neurons, as well as reduced axonal myelination and reduced internodal length, have been considered responsible, at least in part, for the age-related decrease in nerve conduction velocity. Reductions in peripheral efferent and afferent axon action potential conduction velocity have been often reported in the literature [82,[87][88][89][90][91]. Rivner et al [92] demonstrated that advancing age highly correlates with variations of nerve conduction velocity and both motor and sensory responses.…”
Section: Spinal Age-related Adaptationmentioning
confidence: 95%